ANALYSIS OF FLEXURAL STRENGTH OF BEAM USING BAMBOO REINFORCEMENT - FITRA RAHARJA ASHSHIDDIQ; YONAS PRIMA ARGA RUMBYARSO; BERMANDO M SIAGIAN (CV KULTURA DIGITAL MEDIA, 2024)
Concrete is the main material in building construction made from a mixture of gravel, sand, cement, and water. This material is the most commonly used in construction. The development of concrete technology brings various innovations to improve its quality, including the addition of additional materials or substitutes such as bamboo reinforcement. Bamboo reinforcement is an alternative because of its abundant availability, easy to obtain, and economical price, thus offering a more affordable construction solution. Research has explored the use of bamboo as a substitute for steel reinforcement, considering that bamboo has a strong mechanical structure. In Indonesia, Petung, wulung, tali, and Ori bamboo are the most commonly used types. Concrete design standards and compressive strength testing are regulated by SNI, with the quality of concrete tested according to SNI 1974-2011 and the increase in concrete flexural strength measured based on SNI 4431-2011. Bamboo reinforced beams at the age of 7 days reached 25 KN, at the age of 14 days reached 28 KN and at the age of 28 days reached 29 KN. Where it can be concluded that the compressive strength of concrete increases at the age of 7 to 28 days. The bagasse reinforced beam at the age of 7 days reached 20 KN, at the age of 14 days reached 23 KN and at the age of 28 days reached 24 KN. Where it can be concluded that the compressive strength of concrete increased at the age of 7 to 28 days but the results at the age of 28 days did not reach 100%. The iron reinforced beam at the age of 7 days reached 26 KN, at the age of 14 days reached 30 KN and at the age of 28 days reached 33 KN. Where it can be concluded that the compressive strength of concrete increased at the age of 7 to 28 days. Based on the results of the study, it was found that the beam with the addition of bamboo and iron reinforcement experienced an increase in the percentage of flexural strength testing while the beam reinforced with bagasse at the age of 28 days did not reach the desired target.